2022
DOI: 10.1108/jsocm-04-2020-0072
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of safe motherhood practices and the moderating role of facilitating conditions

Abstract: Purpose The purpose of the study is to investigate the factors responsible for the utilisation of safe motherhood practices under the Government of India (GOI)-run maternal health programme Janani Suraksha Yojana (JSY). Design/methodology/approach Data for the survey were collected from 435 expectant mothers registered under JSY from seven districts of western Uttar Pradesh, India. Based on the existing theories of behaviour change and the social marketing framework, a model of antecedents of adoption of saf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Few studies examined the moderating role of FC. For instance, FC was tested as a moderator in the adoption of safe motherhood (Rai & Biswas, 2022). In Saudi Arabia, FC can facilitate the usage of technology and an encouraging factor for such usage.…”
Section: Fc As a Moderatormentioning
confidence: 99%
“…Few studies examined the moderating role of FC. For instance, FC was tested as a moderator in the adoption of safe motherhood (Rai & Biswas, 2022). In Saudi Arabia, FC can facilitate the usage of technology and an encouraging factor for such usage.…”
Section: Fc As a Moderatormentioning
confidence: 99%
“…Social marketing approaches that incorporated the SCT has mostly focussed on parental experiences (Maas et al , 2022; Rai and Biswas, 2022); health behaviour and or food consumption (Harris et al , 2022; McDivitt et al , 2011; Ryan et al , 2022); and more recently, technology related subjects (Saleme et al , 2020). When the SCT has been incorporated regarding pro-environmental behaviours, it has been in conjunction with other theories, such as goal-framing theory (Rohenkohl et al , 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the model of reciprocal interactions, these factors are both influencers on motivation, and motivational outcomes. Self-efficacy plays an important role as part of the behavioural factors, as motivational outcomes can affect people's self-efficacy positively and maintain motivational outcomes.Social marketing approaches that incorporated the SCT has mostly focussed on parental experiences(Maas et al, 2022;Rai and Biswas, 2022); health behaviour and or food consumption(Harris et al, 2022;McDivitt et al, 2011;Ryan et al, 2022); and more recently,…”
mentioning
confidence: 99%
“…Triandis (1979) also suggested that external conditions impact behaviour. Researchers have applied TIB to understand different behaviours, including safe motherhood (Rai & Biswas, 2022), food waste (Jabeen et al, 2023), mobility (Mifsud et al, 2019) and water use (Ibrahim et al, 2018).…”
Section: Theoretical Backgroundmentioning
confidence: 99%